2022
DOI: 10.1038/s41467-022-30893-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing of peripheral blood mononuclear cells reveals widespread, context-specific gene expression regulation upon pathogenic exposure

Abstract: The host’s gene expression and gene regulatory response to pathogen exposure can be influenced by a combination of the host’s genetic background, the type of and exposure time to pathogens. Here we provide a detailed dissection of this using single-cell RNA-sequencing of 1.3M peripheral blood mononuclear cells from 120 individuals, longitudinally exposed to three different pathogens. These analyses indicate that cell-type-specificity is a more prominent factor than pathogen-specificity regarding contexts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 95 publications
4
92
1
Order By: Relevance
“…Context dependency: A context-specific eQTL, invisible in bulk tissue, replaces or supplements the bulk tissue homeostatic eQTL Cell type [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] -Only a subset of cell types in the tissue contribute to the GWAS phenotype.…”
Section: Extended Models Of Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Context dependency: A context-specific eQTL, invisible in bulk tissue, replaces or supplements the bulk tissue homeostatic eQTL Cell type [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] -Only a subset of cell types in the tissue contribute to the GWAS phenotype.…”
Section: Extended Models Of Gene Regulationmentioning
confidence: 99%
“…Cell state or environment 225,227,231,233,[241][242][243][244][245][246][247][248] -The causative eQTL has effects that are undetectable in steadystate expression under normal conditions.…”
Section: Extended Models Of Gene Regulationmentioning
confidence: 99%
“…Existing approaches to link transcription factors (TFs) to their regulatory targets based on gene expression data include tracking gene coexpression across different cell states ( 1 4 ), perturbing TFs experimentally and measuring transcriptomic changes ( 5 8 ), and studying coordinated changes in genes’ expression over dynamic biological processes ( 9 11 ). Single-cell RNA sequencing (scRNA-seq) technologies have made it possible to apply these approaches to study gene expression at unprecedented resolution ( 11 24 ).…”
mentioning
confidence: 99%
“…Studies in peripheral blood mononuclear cells [119], fibroblasts [78], tumor samples [59], and pluripotent and differentiating cells [15, 23, 42, 78] found several eQTLs that would have been missed in bulk sequencing approaches due to being active in only one or a few cell types. While in many single-cell studies most of the detected eQTLs were only found in a single cell type [44, 56, 78], this likely overestimates the overall cell-type specificity of genetic effects on gene expression due to incomplete power of eQTL discovery in these datasets [81]. Previous approaches have successfully mapped the genetic determinants of responses to infection, drugs, and other stimuli [2, 7, 12, 25, 37, 39, 47, 48, 49, 51, 61, 62, 64, 77, 79, 89, 97, 104, 125] using bulk RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…Previous approaches have successfully mapped the genetic determinants of responses to infection, drugs, and other stimuli [2, 7, 12, 25, 37, 39, 47, 48, 49, 51, 61, 62, 64, 77, 79, 89, 97, 104, 125] using bulk RNA-seq. How-ever, these genotype-by-environment (GxE) effects are also likely to be cell-type-specific [28], especially in the context of highly-specialized immune responses, as investigated in recent studies of response eQTL mapping using single cell technology in immune cells exposed to pathogens, bacteria and yeast [81], and influenza A [92]. While different immune stimuli have been studied at single cell resolution; the response to glucocorticoids has not been previously examined.…”
Section: Introductionmentioning
confidence: 99%